A spectrum of non-belonging - refugees, human rights and political pragmatism - Slavnic, Zoran (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2014)
This article represents the analysis of the life history of one of the refugees from Bosnia and Herzegovina who came to Sweden with Croatian passport and, as such, initially received a negative decision to her request for asylum, and then a temporary residence permission for a period of six months. The analysis covers three geographically and temporally separate phases of this refugee odyssey: life during the war and flight, then refugee life in Croatia, and finally refuge in Sweden. The main aims of this article are twofold. Firstly, it aims to show the way refugees themselves look at their refugee life and the role of the various macro-, mezzo- and micro-actors, who in every way influence their life. Secondly, it tries to demonstrate all the possible strategies which the governments of Western Europe try to develop in "solving the refugee problems in situations" where the gulf between their humanitarian rhetoric and real pragmatic politics becomes uncomfortably deep.
Keywords: begunci; etnični konflikti; socialna država; welfare state; državljanstvo; Bosna in Hercegovina; Bosnia and Herzegovina; Švedska; begunska politika